Effect of Randall foils on the rowing propulsive cycle - Cardoso, R.; Fonseca, P.; Goethel, M.; Abraldes, J. A.; Gomes, B. B.; Vilas-Boas, J. P.; Fernandes, R. J. (Sports Biomechanics, 2025)
Rowing performance depends on the design and building materials used for competition. Recently, attempting to improve rowing performance, the Randall foil has been attached to the top edge of a rowing Big blade, making it spoon shaped. The current study aimed to analyse the differences between Big blades with and without Randall foils in force-related variables. Nineteen rowers performed two bouts of 90 s at maximal effort tethered rowing and differences were found in cycle average peak force (4.33 ± 1.46 vs. 5.26 ± 1.57 N/kg), propulsive cycle average time (1.79 ± 0.38 vs. 1.52 ± 0.24 N/kg.s) and rate of force development (8.79 ± 4.75 vs. 12.07 ± 4.60 N/kg/s) for Big blades with and without foils (respectively). Differences were also observed between the middle (4.79 ± 1.21 vs. 4.08 ± 1.48 N/kg) and final phases (4.86 ± 1.45 vs. 4.04 ± 1.47 N/kg) of the rowing effort for the cycle average peak force of Big blades with and without Randall foils. Data suggest a positive effect of these foils on the force-time curve profile. Future studies should focus on testing its influence on free on-water rowing.